2013
DOI: 10.1371/journal.pone.0056582
|View full text |Cite
|
Sign up to set email alerts
|

Efficient E. coli Expression Strategies for Production of Soluble Human Crystallin ALDH3A1

Abstract: Aldehyde dehydrogenase 3A1 (ALDH3A1) is a recently characterized corneal crystallin with its exact functions still being unclear. Expressing recombinant human ALDH3A1 has been difficult in Escherichia coli (E. coli) because of low solubility, yield and insufficient purity issues. In this report, we compared different E. coli expression strategies (namely the maltose binding protein; MBP- and the 6-his-tagged expression systems) under conditions of auto-induction and co-expression with E. coli’s molecular chape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…The diminished protein degradation seems to have been critical for recovery. Modifications of culture conditions and induction time may favor parameters such as reduced molecular hydrophobic interactions, inhibition inclusion body formation, and lower protein synthesis rate, which in turn favor the correct folding and reduce the activity of proteases (58). Thus, the protocol presented in this work for purification of DENV NS5 results in the highest recovery values so far reported.…”
Section: Discussionmentioning
confidence: 95%
“…The diminished protein degradation seems to have been critical for recovery. Modifications of culture conditions and induction time may favor parameters such as reduced molecular hydrophobic interactions, inhibition inclusion body formation, and lower protein synthesis rate, which in turn favor the correct folding and reduce the activity of proteases (58). Thus, the protocol presented in this work for purification of DENV NS5 results in the highest recovery values so far reported.…”
Section: Discussionmentioning
confidence: 95%
“…This methodology previously has been demonstrated to be a highly effective way to increase the soluble expression of various recombinant proteins in E. coli [25, 26], and furthermore using a chaperone transformation strategy [25, 40]. The resulting expression studies showed that two groups of molecular chaperones from E.coli (GroES/GroEL and DnaK/DnaJ/GrpE) were the most effective with greater than 20% of the monomeric cyclin A being expressed in the soluble fraction.…”
Section: Discussionmentioning
confidence: 99%
“…A chaperone expression strategy previously described [25], was exploited to achieve elevated amounts of heterologous soluble over-expression of a 6-His tagged- human protein with the two groups of molecular chaperones from E. coli (GroES/ GroEL and DnaK/DnaJ/GrpE). This strategy resulted in higher yield of the soluble, active and natively folded form of ALDH3A1 [26]. In addition, 3-deoxy-d-arabino-heptulosonate-7-phosphate synthase (DAHPS, from Actinosynnema pretiosum ssp.…”
Section: Introductionmentioning
confidence: 99%
“…The most extensively used chaperone systems that have facilitated protein production in E.coli are DnaK-DnaJ-GrpE and GroEL-GroES[19,20]. In insect cells, host protein biosynthesis shuts down as a result of infection by the recombinant baculovirus, which can adversely affect levels of molecular chaperones important for the folding of secreted proteins and membrane proteins in the endoplasmic reticulum (ER), particularly in relation to the high levels of protein synthesis resulting from high mRNA levels produced from the polyhedrin promoter.…”
Section: Folding and Secretory Pathway Engineeringmentioning
confidence: 99%